Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inlet Guide Vane Wakes on the Passage Flow in a Transonic Axial Compressor

Abstract: Variable inlet guide vanes enhance the efficiency and stability of modern transonic compressors. The current quest for compact and highly efficient aero-engines requires for higher stage-loading and small axial gaps between adjacent blade rows, increasing interaction between blade rows and introducing further unsteadiness into the flow. Modeling these interactions is relevant to jet engine implementation. Recent advancements in numerical simulation of unsteady flow in multiple blade rows create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The smallest variation is seen for conf-B (which features the highest inlet swirl). This supports the observations by Biela et al 24 and Leichtfuss et al, 16 which had shown that conf-B not only has a lower TLF, but also a slightly larger stall margin.…”
Section: Unsteady Wall Pressuresupporting
confidence: 92%
See 3 more Smart Citations
“…The smallest variation is seen for conf-B (which features the highest inlet swirl). This supports the observations by Biela et al 24 and Leichtfuss et al, 16 which had shown that conf-B not only has a lower TLF, but also a slightly larger stall margin.…”
Section: Unsteady Wall Pressuresupporting
confidence: 92%
“…In order to capture these processes in an experiment the application of unsteady wall pressure measurements have been widely used. Inoue et al 15 and Leichtfuss et al 16 show a very good agreement between regions of low wall pressure and the lip leakage vortex. A large number of research groups have used this technique to investigate the unsteady flow features close to the wall.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Others compare steady and unsteady results but only for a single stage and at design speed [7][8][9]. Further single stage unsteady simulations have been presented for part speed calculations [10][11][12] and at design speed [13][14][15][16][17], including Large Eddy Simulations (LES) [18], however, none of these compare the unsteady simulations to steady simulations.…”
Section: Introductionmentioning
confidence: 99%